2013
DOI: 10.7314/apjcp.2013.14.1.309
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Murine-derived GL26 Cells Promote Glioblastoma Tumor Growth by Reducing Number and Function of CD8+T Cells

Abstract: Aim: Brain tumors almost universally have fatal outcomes; new therapeutics are desperately needed and will only come from improved understandins of glioma biology. Methods: Exosomes are endosomally derived 30~100 nm membranous vesicles released from many cell types. Examples from GL26 cells were here purified using density gradient ultracentrifugation and monitored for effects on GL26 tumor growth in C57BL/6j mice (H-2b). Lactate dehydrogenase release assays were used to detect the cytotoxic activity of CD8+T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 32 publications
(27 reference statements)
0
30
0
Order By: Relevance
“…Exosomes and cytokines present in serum of GBM patients promote a Th2 type environment, rich in IL-4, IL-13, and TGF-β, in the peripheral blood [20,21] indicating that tumors exert an immunosuppressive systemic effect beyond the boundaries of the CNS. A previous study revealed that exosomes from murine-derived glioblastoma GL26 cell line promote tumor growth by inhibiting the number and function of cytotoxic CD8 + T cells in vivo [22]. Moreover, GBM-derived vesicles affect cytokine output and migratory capabilities of mitogen-stimulated healthy peripheral blood mononuclear cells (PBMCs) [23] and skew the differentiation of peripheral blood-derived monocytes to alternatively activated M2 tumor-supportive macrophages [24].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes and cytokines present in serum of GBM patients promote a Th2 type environment, rich in IL-4, IL-13, and TGF-β, in the peripheral blood [20,21] indicating that tumors exert an immunosuppressive systemic effect beyond the boundaries of the CNS. A previous study revealed that exosomes from murine-derived glioblastoma GL26 cell line promote tumor growth by inhibiting the number and function of cytotoxic CD8 + T cells in vivo [22]. Moreover, GBM-derived vesicles affect cytokine output and migratory capabilities of mitogen-stimulated healthy peripheral blood mononuclear cells (PBMCs) [23] and skew the differentiation of peripheral blood-derived monocytes to alternatively activated M2 tumor-supportive macrophages [24].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers found overexpression of Mda-9/ syntenin could promote the migration ability of glioma cells (Zhong et al, 2012), someone found two kinds of circadian clock genes, cry1 and cry2, played crucial roles in the survival of human glioma cells (Luo et al, 2011) . Recently, exosomes, cell-derived vesicles which were reported containing TDP-43 inclusion, was found to be promote glioma cells' growth by inhibiting CD8+ T cells (Liu et al, 2013). Yet many related proteins and genes remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells can not only remove malignant cells in the body, but also can play an immune surveillance role in tumorigenesis, directly inhibit tumor cell growth and prevent metastasis of tumor and tiny cancer embolus so that they play a very important role in the body's antitumor immunity (Holt et al, 2011). Therefore, the detected percentages of T cell subsets and NK cells in plasma can represent changes of lymphocytes in circulation and are effective indicators to reflect postoperative cellular immune function in tumor patients and to have important value for determining the prognosis of tumor patients after operations (Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%